Gestión de incidentes y su relación en la calidad de los servicios TI en la oficina de recursos humanos de la Universidad Nacional de la Amazonía Peruana 2018 - Torres Tapullima, William Franchesco (2018)
Research your objective: Determine the relationship that exists between Incident and Problem Management Processes according to ITIL V3.0 and the Quality of IT Services in the human resources office of the National University of the Peruvian Amazon 2018. the investigation belongs to the correlational descriptive type and with non-experimental research design and to the specific correlational transactional design. According to the objectives of the project, Population was determined as a unit of study: 160 users and with a sample of 57 in the human resources office of the National University of the Peruvian Amazon chosen for convenience. The survey technique was used for the data collection process and a questionnaire was used as an instrument. For the processing and analysis of data, the techniques of descriptive statistics and inferential non-parametric chi square statistics were used, using the Excel spreadsheet. To test the Research Hypothesis, the chi square statistical test was used. X^2^c =8.39 > X^2^t=3.325 and with degree of freedom (Gl =9) α =0.05%, NC = 0.95%, observando que∶ X^2^c > X^2^t showing that there is a relationship between Processes Management of Incidents and Problems according to ITIL V3.0 and the Quality of the IT Services, accepting the general hypothesis of the investigation: The Processes Management of Incidents and Problems according to ITIL V3.0 has statistically significant relation with the Quality of the Services of IT in the human resources office of the National University of the Peruvian Amazon 2018.